Mortality associated with lithium and valproate treatment of US Veterans Health Administration patients with mental disorders. (July 2015) - Smith, Eric G.; Austin, Karen L.; Kim, Hyungjin Myra; Eisen, Susan V.; Kilbourne, Amy M.; Miller, Donald R.; Zivin, Kara; Hannemann, Claire; Sauer, Brian C.; Valenstein, Marcia
Abstract : Background: The mood stabilisers lithium and valproate might plausibly have differing associations with mortality because of differing effects on mental health and various physiological indicators. Aims: To assess associations between lithium, valproate and non-suicide mortality. Method: Intention-to-treat, propensity score-matched cohort study. Results: Lithium was associated with significantly reduced non-suicide mortality in the intent-to-treat cohort over 0–90 days (hazard ratio (HR) = 0.67, 95% CI 0.51–0.87) but not longer. In secondary analyses, a sizeable reduction in mortality was observed during active treatment with lithium across all time periods studied (for example 365-day HR = 0.62, 95% CI 0.45–0.84), but significantly increased risks were observed among patients discontinuing lithium by 180 days (HR = 1.54, 95% CI 1.01–2.37). Conclusions: Patients initiating lithium had lower non-suicide mortality over 0–90 days than patients initiating valproate and consistently lower non-suicide mortality among patients maintaining treatment, but elevated risk among patients discontinuing treatment by 180 days. Although residual confounding or selection effects cannot be excluded, this study suggests potential benefits to enhancing lithium treatment persistence and the monitoring of patients discontinuing lithium. There is a need for further research.